Bildungspolitik ist Arbeitsmarktpolitik - Ingo Eduard Isphording; Dirk Zorn (Wirtschaftsdienst, 2024)
– Based on empirical evidence, we argue that recent declines in the basic skills of German pupils are highly concerning from a labour market policy perspective. High-quality schooling is crucial for meeting the demands of a changing labour market, as it provides new cohorts of workers with basic and self-productive skills and facilitates the acquisition of more complex skills and lifelong metacompetences. Therefore, education policy must be seen as an integral part of labour market policy. However, there is a distinct lack of communication and coordination between labour and education policy in Germany, due to misaligned incentives and fragmented responsibilities. Recent reforms provide hope that the necessary capacity building can be achieved.
Keywords: H52; I21; I28; 330; Bildungspolitik; Arbeitsmarktpolitik; Deutschland; Bildungspolitik; Arbeitsmarktpolitik; Deutschland